Efektifitas Standar Prosedur Operasional Terhadap Penurunan Waktu Tunggu Operasi Elektif di Rumah Sakit Umum - Fransiska Leny Aweq; Nono Ifantono; Lukman Hakim (Universitas Muhammadiyah Yogyakarta, 2017)
This research used quasi-experimental design with pre and post test design. Then, for the method used in this research was pre and post intervention which analyze the primer data and secondary data. Furthermore, the research also used descriptive approach to compare the result of pre and post the standard operating procedure was socialized. This research used 52 people as the sample. The research about waiting time of elective surgery and find the main problem bring in the chosen solution by the researcher which is this solution showed the result of the comparison in pre and post socialization the standard operating procedure that increases about 25%. This comparison showed that there is an enhancement of the number of staffs in the operating room who could performance the surgery on time and also showed the reduction number of waiting time in elective surgery.